(untitled) (Bangladesh Journal of Botany, 2025)
Finger millet porridge, a traditional lactic acid fermented drink prepared from the minor millet Eleusine coracana (L.) has many nutritional and health benefits. In this study, the finger millet porridge was prepared, and probioticated with free and encapsulated cells of the selected probiotic cultures viz., Lactobacillus acidophilus NCDC 14 and Lactobacillus casei NCDC 298 to increase its functionality. The probiotic load of the porridge was 1010 cfu g-1 and based on a 9-point hedonic scale sensory evaluation, a maximum score was obtained for 8h of fermentation time (8.9) irrespective of the treatments. In this study, it was observed that phytic acid decreased whereas the bioavailability of minerals viz., calcium, iron and zinc and reducing sugars were increased. The probiotic cultures were viable (109 cfu g-1) in the fermented finger millet porridge during 7 days of refrigerated storage with more viability in alginate-encapsulated cells. Bangladesh J. Bot. 54(1): 75-81, 2025 (March)